(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
ملخص: هدفت الدراسة الحالية للتعرف على الخصائص السيكومترية لمقياس اتخاذ القرار المهني، واستخراج معايير أداء تمكننا من تفسير نتائج الدرجات الخام للتلاميذ، لتحقيق هذا الهدف تم اختيار عينة الدراسة مكونة من 100 تلميذ تلميذة سنة رابعة متوسط، تم اختيارهم بطريقة العشوائية البسيطة، باستخدام مقياس krits، وللتأكد من الصدق تم استخدام أساليب متعددة وهي: الاتساق الذاتي وذلك من خلال ايجاد معاملات ارتباط بين كل بند من بنود المقياس، والتحليل العاملي، أما بالنسبة لمؤشرات الثبات فقد تم استخدام معامل ألفا كرومباخ والتجزئة النصفية. توصلت النتائج الدراسة إلى: تمتع المقياس بخصائص سيكومترية: *الصدق: لقد تم حساب صدق الاتساق الداخلي وتراوحت معاملات الارتباط بين بنود المقياس والدرجة الكلية ما بين (0.20-0.59). علاوة على ذلك؛ صدق التحليل العاملي الاستكشافي عن طريق مصفوفة العوامل بعد التدوير والتي تراوحت معاملاتها بين(0.30) و(0.54). *الثبات: تمتع مقياس اتخاذ قرار المهني بمؤشرات ثبات مقبولة والتي حسبت عن طريق ألفا كرومباخ وطريقة التجزئة النصفية وكلاهما نفس القيمة وهي (0.68)، وهو صادق وثابت. كلمات دالة: قرار- اتخاذ قرار- اتخاذ اقرار المهني –صدق -ثبات. Abstract: The present study aimed to identify the psychometric properties of the professional decision-making scale, and to extract performance standards that enable us to interpret the results of the raw grades of the students. To achieve this goal, the study sample was chosen consisting of 100 intermediate fourth-year pupils, They were chosen by simple randomization, using the Krits scale and to ensure validity The use of multiple methods, which are: the self-consistency by finding correlation coefficients between each of the scale items, Factor analysis As for Stability indicators, the Alpha Cronbach coefficient and the half segmentation were used. The results of the study concluded: The scale has psychometric properties: * validity: The validity of the internal consistency was calculated, and the correlation coefficients ranged between the scale items and the total score between (0.20-0.59). Furthermore it; The validation of the exploratory factor analysis through the factor matrix after rotation, whose coefficients ranged between (0.30) and (0.54). * Stability: The professional decision-making scale has acceptable reliability indicators that were calculated by Alpha Cronbach and the half-segmentation method, both of which are the same value (0.68), which is validity and Stability. Key words: decision-making-decision-making-professional decision-making -validity- Stability.